2016
DOI: 10.1364/oe.24.007728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thickness disorder on the performance of photonic crystal surface wave sensors

Abstract: We investigated experimentally and numerically the robustness of optical sensors based on Bloch waves at the surface of periodic one-dimensional photonic crystals. The distributions of sensor characteristics caused by the fabrication uncertainties in dielectric layer thicknesses have been analyzed and robustness criteria have been set forth and discussed. We show that the performance of the surface wave sensors is sufficiently robust with respect to the changes of the photonic crystal layer thicknesses. Layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…While the latter is a unique and valuable feature of label-free methods, resolution is usually lower compared to the fluorescence-based methods (Mathias et al, 2007). For such a reason, fluorescence schemes exploiting evanescent waves, featuring strong field localization and intensity enhancement at the surface of interest, have been employed (Anopchenko et al, 2016;Cooper, 2002;Descrovi et al, 2013;Fan et al, 2008;Ligler and Taitt, 2008;Zhao et al, 2010). Among evanescent wave sensors, those based on Bloch surface waves (BSW) sustained by dielectric one dimensional photonic crystals (1DPC) (Yeh et al, 1977) have been demonstrated as an effective alternative to SPR for label-free optical biosensing (Konopsky et al, 2013;Rivolo et al, 2012;Rizzo et al, 2014;Shinn and Robertson, 2005;Sinibaldi et al, 2015aSinibaldi et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…While the latter is a unique and valuable feature of label-free methods, resolution is usually lower compared to the fluorescence-based methods (Mathias et al, 2007). For such a reason, fluorescence schemes exploiting evanescent waves, featuring strong field localization and intensity enhancement at the surface of interest, have been employed (Anopchenko et al, 2016;Cooper, 2002;Descrovi et al, 2013;Fan et al, 2008;Ligler and Taitt, 2008;Zhao et al, 2010). Among evanescent wave sensors, those based on Bloch surface waves (BSW) sustained by dielectric one dimensional photonic crystals (1DPC) (Yeh et al, 1977) have been demonstrated as an effective alternative to SPR for label-free optical biosensing (Konopsky et al, 2013;Rivolo et al, 2012;Rizzo et al, 2014;Shinn and Robertson, 2005;Sinibaldi et al, 2015aSinibaldi et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…2c, most likely due to a difference of the two top layers' thicknesses from the values given above for the design structure. The fabrication tolerances are in fact not small enough to guarantee that such thicknesses are effectively 20 nm [27]. As expected, the BSW dip shifts when different liquids are used, owing to their different refractive index.…”
Section: Optical Setupmentioning
confidence: 86%
“…Numerical simulations of the waveguide structure were carried out using the MODE Solutions software from Lumerical Solutions, Inc. The effective index of the ENZ mode supported by three layer structures was calculated using of a MATLAB code developed by G. Figliozzi and F. Michelotti at the University of Rome "La Sapienza" (Italy) 44 based on the transfer matrix method 45 . In all simulations, permittivity function of silica is modeled using the Palik data 46 .…”
Section: Methodsmentioning
confidence: 99%